2001
DOI: 10.1097/00000539-200104000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactically-Administered Rectal Acetaminophen Does Not Reduce Postoperative Opioid Requirements in Infants and Small Children Undergoing Elective Cleft Palate Repair

Abstract: Acetaminophen is widely used prophylactically for postoperative analgesia in children and is thought to have an opioid-sparing effect. We showed that rectal acetaminophen up to 40 mg/kg administered at anesthesia induction lacked proof of efficacy, whereas IV opioid boluses resulted in reliable pain relief in children undergoing cleft palate repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 21 publications
0
57
0
5
Order By: Relevance
“…Yet, there is a paucity of research relating to the benefits of orally and rectally administered acetaminophen in neonates and infants. Findings from the few studies including newborn or young infants have generally shown little analgesic benefits [41][42][43][44]. Well-conducted studies of enterally administered acetaminophen, given alone or in combination with other analgesics, are required to address this knowledge gap.…”
Section: Acetaminophenmentioning
confidence: 99%
“…Yet, there is a paucity of research relating to the benefits of orally and rectally administered acetaminophen in neonates and infants. Findings from the few studies including newborn or young infants have generally shown little analgesic benefits [41][42][43][44]. Well-conducted studies of enterally administered acetaminophen, given alone or in combination with other analgesics, are required to address this knowledge gap.…”
Section: Acetaminophenmentioning
confidence: 99%
“…. ,46± 49,52±54] that examined pre-emptive analgesia, as de®ned above (Table 3) [15] 2001 DB, DA [16] 2001 MP [17] 2002 A NSAIDs [18] 2001 DA [19] 2002 P [20] 2002 DB Opioids [21] 2001 DA NMDA antagonists [22] 2001 P [23] 2001 MP [24] 2001 P [25] 2001 P Tricyclic antidepressants [26] 2001 DA, MP Local anesthetics and opioids [27] 2001 DB [28] 2002 DB [29] 2001 DA Local anesthetics and NSAIDs [30] 2001 DB…”
Section: Pre-emptive Analgesiamentioning
confidence: 99%
“…Lediglich zwei Untersuchungen beziehen sich offensichtlich auf in Deutschland verbreitete Präparate wie z. B. ben-u-ron ® [26,87].…”
Section: Orale Gabeunclassified
“…Klar erscheint lediglich, dass Paracetamol als Monoanalgetikum in einer Dosis von bis zu 20 mg/kg KG bei Kindern zur postoperativen Schmerztherapie, unabhängig vom operativen Eingriff, nicht ausreicht [18,63,66,77,78,85,88]. Demgegenüber zeigt sich, bis auf eine Ausnahme [26], bei Initialdosen von >35 mg/kg KG ein durchweg guter analgetischer Effekt [8,24,49,56,82].…”
Section: Kritische Wertung Der Literatur Unter Klinischen Aspekten Zuunclassified